Climate Change and The Spread Of Dengue Fever : Risk Evaluation and Mitigation Efforts in Sumba Tengah Regency - Fitriah, Yunita (BKM Public Health and Community Medicine, 2024)
Climate change has become a significant global challenge that can affect public health and increase the risk of vector-borne disease such as dengue fever. Changes in temperature and weather patterns have created more favorable conditions for the Aedes Aegypti mosquitoes, the vectors of dengue fever. Sumba Tengah, like many othe regions has also experienced changes in weather patterns, creating conditions conducive to the breeding of Aedes Aegypti mosquitoes. Risk evaluation shows that climate change accelerates the mosquitoe life cycle and expands their distribution area, increasing the incidence of dengue fever cases in Sumba Tengah Regency. The community of Sumba Tengah faces significant challenges in addressing the rise in dengue fever cases. Limited healthcare systems and low public awareness exacerbate the situation. Therefore, comprehensive mitigation efforts are urgently needed. The first necessary action is to utilize the Early Warning Alert and Response System (EWARS) reporting application for monitoring and predicting outbreaks. This will enable a quick response and more effective control measures. The next step to be taken is to conduct educational campaigns for the community to enhance their understanding of dengue fever prevention and the relationship between climate change and dengue fever incidence. With better knowledge, the community can take more proactive preventive measures such as eradicating mosquito breeding sites. Increasing cross-sector collaboration is the next step that can be taken. The involvement of various stakeholders, including the health sector and village governments, is crucial to creating a coordinated and sustainable approach. Government policies must also support this effort by providing the necessary resources and regulations to mitigate the impact to the continuously rising incidence of dengue fever in the community. Conclusion is climate change has significantly increased the risk of dengue fever spread in Sumba Tengah Regency. Mitigation efforts involving technology, education and cross-sector collaboration are key to reducing the risk.